Social exclusion among problem drug users - Brandová, Nikola; Kajanová, Alena (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2015)
The survey report presents a summary of the acquired knowledge about social exclusion in the context of problematic drug users. The data are based on a secondary data analysis, in which scientific articles were searched for regarding the period between 2003 and 2014 in databases EBSCO, Scopus and PubMed. We used the fallowing keywords. drug users- social exclusion-addiction. We also used information obtained from printed expert sources and monographs. In the literature, there are two views on the connection of substance abuse and the phenomenon of social exclusion. The first one is devoted to social exclusion as a consequence of problematic drug use. The second view is focused on the opposite sequence of those phenomena - thinking about social exclusion as a cause of problematic use of addictive substances. Both of the above views are closely linked and in practice are connected.
Keywords: social exclusion; drug users; consequences of drug using; disadvantage